2022
DOI: 10.3390/ma15176181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multi-Walled Carbon Nanotubes and Carbon Fiber Reinforcements on the Mechanical and Tribological Behavior of Hybrid Mg-AZ91D Nanocomposites

Abstract: Magnesium matrix composites are extensively used in automotive and structural applications due to their low density, high strength, and wear-resistant properties. To reach the scope of industry needs, research is carried out regarding enhancing the mechanical and tribological behavior of the magnesium composites by reinforcing the nano-sized reinforcements. In the present work, research has been carried out to enhance the properties of the magnesium AZ91D hybrid composite by reinforcing carbon fibers (CFs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…CNTs and TiB 2 microparticles may contribute to the dual-reinforced composite's mechanical strength [46]. As a result, load transfer, grain refinement of TiB 2 microparticles and CNTs, and hybrid reinforcement thermal mismatch all played a role in the impact of hybrid reinforcements on AZ91D matrix composites [47].…”
Section: Resultsmentioning
confidence: 99%
“…CNTs and TiB 2 microparticles may contribute to the dual-reinforced composite's mechanical strength [46]. As a result, load transfer, grain refinement of TiB 2 microparticles and CNTs, and hybrid reinforcement thermal mismatch all played a role in the impact of hybrid reinforcements on AZ91D matrix composites [47].…”
Section: Resultsmentioning
confidence: 99%
“…This verifies the wear rate of the 20/0.5 sample is higher than that of other samples. It is well known that the uniform distribution of the reinforcement particles is required to improve tribological performance [127][128][129]. The authors reported that the agglomeration of CNT deteriorated the tribological performance.…”
Section: Worn Surface Analysismentioning
confidence: 99%
“…CNTs are effective as additives to improve the tribological properties of blocky composites [32]. Researchers are exploring their applications in chemical catalysis, energy conservation, and other fields [33]. However, while CNTs enhance the strength performance of blocky composite materials, there are also drawbacks such as poor dispersion and weak adhesion to the substrate surface which affect their level of enhancing wear-resistance properties of blocky composites.…”
Section: Introductionmentioning
confidence: 99%